Some properties of the one-dimensional potentials - Kalmenov, T.Sh.; Kadirbek, A.; Kydyrbaikyzy, A. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The main aim of this paper is to study the properties of the one-dimensional potentials. In this paper, we have studied the connection between the one-dimensional potentials and the self-adjoint part of the operator L􀀀1 K , which L􀀀1 K is the solution to the one-dimensional Cauchy problem. Moreover, a new method is used that allows us to reduce the spectral problem for the Helmholtz potential to the equivalent problem.
Бірөлшемді потенциалдардың кейбір қасиеттері
Некоторые свойства одномерных потенциалов
Keywords: one-dimensional Helmholtz potential; spectral problem; Fredholm operator